Effectiveness of project-based learning in improving science literacy and collaborative skills of Muhammadiyah middle school students - Iin Hindun; N. Nurwidodo; Sri Wahyuni; Nur Fauziah (JPBI (Jurnal Pendidikan Biologi Indonesia))
Science literacy abilities and collaborative skills are part of the life skills demands of the 21st century. This research aims to analyze the effectiveness of the PjBL learning model in improving the Science literacy and collaborative skills of students at Muhammadiyah 2 Middle School, Batu City and Muhammadiyah 8 Middle School, Batu City. The research design uses Pretest-Posttest Control Group Design. The research sample consisted of 60 class VIII students taken by total sampling. Data was obtained through observation, questionnaires and tests. Data analysis uses covariance analysis (ANCOVA) to verify the data against the proposed hypothesis. The research results show that the average Science literacy and collaboration in PjBL learning is higher than conventional learning. The results of the analysis can be concluded that the implementation of PjBL effectively influences students' Science literacy and students' collaboration skills. Thus, the PjBL model is recommended to be implemented to support the implementation of the Independent Curriculum at the junior high school level as an effort to develop students' 21st century life skills.